Pengaruh Kualitas Produk, Promosi dan Persepsi Harga terhadap Keputusan Pembelian di Kopi Kren Jakarta - Bintang Maha Putri Yudo Negoro; Hadi Wasino (Human Capital Development, 2023)
This research aims to determine the influence of product quality, promotion and price perception on purchasing decisions at Kopi Kren Jakarta. The approach used in this research is a quantitative approach with a total sample size of 160 with the sampling technique used is purposive sampling technique. The measuring tool used in this research is a questionnaire distributed via Google Form. The analysis used includes validity tests, reliability tests, t tests and f tests. The results of the analysis show that: Product quality influences purchasing decisions, promotions and price perceptions also significantly and simultaneously influence purchasing decisions.